EBCOG position statement – Public health role of sexual health and relationships education. (March 2019) - Cameron, Sharon; Cooper, Michelle; Kerr, Yvonne; Mahmood, Tahir
Abstract: Sexual and relationship education should be part of educational curriculum in early teenage years. The young people should be provided with evidence based education to reduce the risks of untimed pregnancies and sexually transmitted infections.